PENINGKATAN ANGKA HARAPAN HIDUP DENGAN PENDETEKSI MASKER BERBASIS TENSORFLOW SEBAGAI UPAYA PENINGKATAN KESADARAN INDIVIDU PUSKESMAS - Dewi Yanti; Barry Ceasar Octariadi; Linda Suwarni (Jurnal Abdi Insani, 2023)
The community service carried out at the UPT Puskesmas Parit H. Husin II was carried out in order to increase individual awareness in the community to continue using masks in the puskesmas area to prevent the transmission of ISPA, TBC and Covid, especially during the smog season due to the forest fires. Apart from that, this service also aims to ensure that health care staff are not overwhelmed in reminding visitors to wear masks one by one at all times so as to create a comfortable environment for visitors who are vulnerable to infection, such as pregnant women, babies, toddlers and the elderly. The method used during service activities is starting from the planning stage, preparation stage, implementation stage and evaluation stage to adjust field conditions with appropriate Tensorflow-based mask detection technology. From the survey results obtained at the beginning before installation (pre-event) and after installation (post-event), information was obtained that the indicators measured in this service activity had been achieved above the 70% standard so it could be concluded that this service activity produced good results. good enough. This can also be seen in visitors who are starting to orderly wear masks when entering the community health center area and also in the responses from visitors and health care staff on the questionnaire who feel that the community health center environment is more comfortable with the presence of mask detectors which can remind or encourage people to continue using masks, 93%.